Cross-Border M&A performance by Chinese firms : industry effect analysis - Ryhänen, Santeri (2017)
Chinese firms participate in cross-border mergers and acquisitions (CBMA) in a constantly increasing rate. As China, the leading developing economy of the world keeps developing, the dynamics of value creation through CBMA change. This study examines the short-term performance of 41 CBMA deals by Chinese firms from 2012 to 2015. Results from the event study analysis show that, on average, Chinese companies should participate in CBMA. The first result of this study indicates that Chinese acquirer companies gain significant cumula-tive average abnormal returns (CAARs) from CBMA. The second result of this study is that Chinese acquirer companies gain bigger CAARs from CBMA when the acquiring firm and the target firm operate in different industries. These findings, along with the existing literature about Chinese CBMA, indi-cate that examination of Chinese CBMA performance requires several factors to be taken into account in order to determine which firms and which industries are in the best position to create value.